2021
DOI: 10.3389/fimmu.2021.640778
|View full text |Cite
|
Sign up to set email alerts
|

Illumination of Molecular Pathways in Multiple Sclerosis Lesions and the Immune Mechanism of Matrine Treatment in EAE, a Mouse Model of MS

Abstract: The etiology of multiple sclerosis (MS) is not clear, and the treatment of MS presents a great challenge. This study aimed to investigate the pathogenesis and potential therapeutic targets of MS and to define target genes of matrine, a quinolizidine alkaloid component derived from the root of Sophorae flavescens that effectively suppressed experimental autoimmune encephalomyelitis (EAE), an animal model of MS. To this end, the GSE108000 gene data set in the Gene Expression Omnibus Database, which included 7 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Our analysis also showed the shorter overall survival in patients with low expression of SFN in BC. Furthermore, SFN could be positively implicated as an oncogene in a variety of diseases, including Alzheimer's disease, Parkinsonian syndromes, and autoimmune disorders affecting the central nervous system [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also showed the shorter overall survival in patients with low expression of SFN in BC. Furthermore, SFN could be positively implicated as an oncogene in a variety of diseases, including Alzheimer's disease, Parkinsonian syndromes, and autoimmune disorders affecting the central nervous system [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, research studies revealed their impressive antimicrobial [ 6 , 8 , 177 ], antifungal [ 6 , 8 , 111 , 112 ], and antimycobacterial [ 10 , 178 ] effects, and some of them displayed activity superior or comparable to those presented by chloramphenicol [ 112 ], amphotericin B [ 115 ], and rifampin [ 124 ]—drugs used in standard therapeutic regimens. Moreover, naphthyridines were shown to present significant properties including antiinfectious: antiviral [ 11 , 24 , 50 , 51 ], antiparasitic [ 9 , 176 ], and antimalarial [ 113 ]; anticancer [ 5 , 6 , 23 , 35 ]; influencing cardiovascular system: hypotensive [ 16 , 27 ], cardioprotective [ 43 , 44 ]; neurological: sedative [ 94 ], analgesic [ 15 ], anticonvulsant [ 78 ], stimulating neuritogenesis [ 188 ]; psychotropic: antianxiety [ 97 ], antidepressant [ 29 , 97 ]; and affecting immune system: anti-inflammatory [ 7 , 56 , 57 ], immunosuppressant [ 48 , 49 , 50 ]. The spectrum of activity of naturally-derived naphthyridines is wide, thus these compounds are undeniably fascinating subjects of research.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 30 was also reported to decrease total bilirubin level and improve survival rates in liver transplant recipients [ 47 ]. Matrine 30 is also considered a promising candidate as an immunosuppressive drug due to inhibiting autoimmune response in experimental models of multiple sclerosis [ 48 , 49 ]. It also exerts antiviral activity [ 50 , 51 ].…”
Section: Naturally Occurring Naphthyridine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term use of MS medications is costly and may cause certain side effects, such as liver injury, lymphopenia, and infections ( Antonazzo et al., 2019 ; Moiola et al., 2020 ). Importantly, recent studies have found that some types of traditional herbal medicine can ameliorate clinical severity and reduce the frequency of clinical exacerbations in relapsing MS with fewer side effects and minor financial burdens ( Kou et al., 2014 ; Zhou and Fan, 2015 ; Dou et al., 2021 ; Zha et al., 2021 ). Therefore, natural products may be a promising treatment for MS.…”
Section: Introductionmentioning
confidence: 99%